Pengembangan kompetensi dalam menunjang tugas pokok dan fungsi aparatur pemerintah pada badan koordinasi wilayah pemerintahan dan pembangunan - Achmad Reza Fachrizi (Faculty of Social and Political Science, Universitas Airlangga, 2016)
Work target for Regional Coordinating Bodies (Badan Koordinasi Wilayah/Bakorwil) is not generally realized as it targeted. As an institution with main duties in government development program in the area, there is a strong need to increase Bakorwil Pamekasan personal competence. This article analyzes to what extent officer competence development in Bakorwil Pamekasan and to review factors that influence officer competence development. This research method used was descriptive qualitative. The sample was collected by purposive sampling technique. In this research, Head of Bakorwil Pamekasan, Secretary of Bakorwil, and all the head division in Bakorwil were choosen as informant. Findings show that competency development in Bakorwil had not yet entirely implemented. There are several factors that hinder the competency development, namely: trust and value, skill/expertness, experiences, personal characteristics, motivation, emotional issues and intellectual capacity. This research concludes that the competency development program was still limited to work meeting, technical meeting, congress, seminar, technical guidance, and workshop. Officer's knowledge about their responsibility and work programs were limited. Moreover, further understanding for work program implementation was not yet fully understood.